Anatomia de la corteza de tres especies de leguminosas I. Origen y desarrollo - Orduño Cruz, A.=700 1 Terrazas, T.
(Es, En)
Ilus., 26 ref.
Keywords: ANATOMIA DE LA MADERA; CORTEZA; PROCEDENCIA; LEGUMINOSAS; PITHECELLOBIUM; ACACIA; MEXICO; DESARROLLO DE LA CORTEZA